Bimbingan Berwirausaha bagi Anggota Koperasi PERMATA NGIJO di Era Digital - Moechammad Sarosa; Waluyo; Dodit Suprianto; Putri Elfa Masudia; Ayu Sulasari; Septriandi Wirayoga; Azis, Yunia Mulyani (Universitas Pendidikan Ganesha, 2024)
Koperasi Simpan Pinjam (KSP)